The Traumatic brain injuries in sports - neurological aspects - Paziewska, Adrianna Marta; Jurasz, Karolina; Cymer, Radosław; Rzeska, Ewa; Rogulski, Michał (Journal of Education, Health and Sport, 2024)
Traumatic Brain Injury (TBI) was characterized as alternation in brain function or any other sign of brain pathology resulting from external force. Sport-related traumatic brain injury (SR-TBI) calculated as up to 20% of all TBA. Different diagnostic tools, such as CT scan or MRI, are utilized in clinical assessment of the patients, however there is a necessity of further investigation of new diagnostic methods such as biomarkers. A long-term repetitive brain injury can lead in consequence to a Chronic Traumatic Encephalopathy (CTE). Neuroprotection, treatment and rehabilitation play a crucial role in both prevention and recovery of TBI patients.